العقوبات الاقتصاديّة أحد أساليب الإرهاب الاقتصادي غير المنظّم (العراق نموذجاً خضع للعقوبات الاقتصاديّة) - قنوع, نزار; الخطيب, دريد; عاقل, منال علي (Latakia University Journal - Economic and Legal Sciences Series, 2013)
يتناول البحث إحدى آليّات الإرهاب الاقتصادي غير المنظّم، والذي يُعَدُ الشّكل المُكمّل للإرهاب الاقتصادي المنظّم الذي تمارسه المنظّمات الدّوليّة كصندوق النّقد الدّولي، البنك الدّولي، ومنظّمة التجّارة العالميّة، أمّا هذا الشّكل غير المنظّم للإرهاب الاقتصادي يُمارَس من قِبَل دولة أو أكثر ضدّ دولة أخرى أو مجموعة دول، ومن ممارساته الحروب الاقتصاديّة، والعقوبات الاقتصاديّة محور بحثنا. يتطرّق البحث إلى مفهوم العقوبات الاقتصاديّة وأشكالها، والإطار القانوني لتلك العقوبات من منظور القانون الدّولي، وبالتّالي الشّروط التي يجب أن تؤخذ بعين الاعتبار لتطبيق العقوبات، لنصل دراسة العراق كنموذج تم تطبيق العقوبات الاقتصاديّة عليه، وبالتّالي إظهار الآثار الكارثيّة التي حقّقتها تلك العقوبات بحقّ الشّعب أوّلاً على الصّعيد الاجتماعي والاقتصادي، وتبيان ما هي الأسباب الحقيقية الكامنة وراء فرض العقوبات، والتي طالما كانت أسباباً سياسيّة، لا علاقة لها للأسباب المُعلنة. The research discusses one of the mechanisms of the unregulated economic terror, which considered the supplementing shape of regulated economic terror practiced by international organizations such as the IMF, World Bank, World Trade Organization, but this shape of unregulated economic terror practiced by a state or more against another state or group of states, and the economic wars, and economic sanctions the focus of our research are part of its practices. The research addresses the concept of economic sanctions and its forms, and the legal framework for these sanctions from the perspective of international law, and therefore the conditions that must be taken into consideration for the application of sanctions, to get to study Iraq as a model that these economic sanctions were applied, and thus show the disastrous effects achieved by these sanctions against the people first on the social and economic level, and show what the real reasons behind the imposition of sanctions, which has long been political reasons, unrelated to the stated reasons.